2010
DOI: 10.1002/sia.3373
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal annealing on the structure and optical properties of d.c. magnetron sputtered titanium dioxide thin films

Abstract: Titanium dioxide (TiO 2 ) thin films were deposited on glass substrate by d.c. magnetron sputtering at 200• C substrate temperature. The thicknesses of the films were measured using stylus type profilometer. The deposited films were annealed using rapid thermal annealing (RTA) system in the O 2 ambient for 20 min at 400 and 500• C. Influence of Ar/O 2 flux ratio and annealing temperature on structural and optical properties of the samples was analyzed using X-ray diffraction (XRD) and UV-vis spectrometer in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…High-temperature annealing was carried out in an oxygen environment to reduce the oxygen vacancy in Nb: TiO 2−x [32,64]. Oxygen atoms could diffuse into the film at high temperatures and occupy oxygen vacancies [65][66][67]. The diffusion mechanism of oxygen during annealing in the oxygen atmosphere is exhibited in figure 14(a).…”
Section: Thermal Stability Of Nb-tio 2−xmentioning
confidence: 99%
“…High-temperature annealing was carried out in an oxygen environment to reduce the oxygen vacancy in Nb: TiO 2−x [32,64]. Oxygen atoms could diffuse into the film at high temperatures and occupy oxygen vacancies [65][66][67]. The diffusion mechanism of oxygen during annealing in the oxygen atmosphere is exhibited in figure 14(a).…”
Section: Thermal Stability Of Nb-tio 2−xmentioning
confidence: 99%
“…Wang et al showed that rutile crystalline phases also possess photocatalytic ability [13]. The crystalline phase transformation, crystalline size, and photocatalytic changes of TiO 2 during the annealing process are also different for TiO 2 prepared by different preparation methods [7,[14][15][16]. Therefore, a comparison of the physical structural, optical, and photocatalytic properties of TiO 2 thin films prepared by different preparation methods during the annealing process needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…To further reduce the oxygen vacancies in the Nb:TiO 2−x sample, high-temperature annealing has been carried out in an oxygen atmosphere [20,21]. Since, in this case, the oxygen atoms can diffuse into the film and occupy the positions of oxygen vacancies, given that, in the traditional vacancy model, diffusion is easily achieved by an adjacent oxygen ion jumping into a vacant site [22][23][24][25]. The proposed oxygen diffusion mechanism through the annealing process in the oxygen atmosphere is depicted in figure 1.…”
Section: Introductionmentioning
confidence: 99%